Selective oxidation of (hetero)sulfides with molecular oxygen under clean conditions - Liu, Kai-Jian; Deng, Ji-Hui; Yang, Jie; Gong, Shao-Feng; Lin, Ying-Wu; He, Jun-Yi; Cao, Zhong; He, Wei-Min (Green chemistry : an international journal and green chemistry resource : GC, 2020)
The development of eco-friendly and switchable catalytic systems for the conversion of a sole raw-material into distinct high-value products is a particularly attractive concept and a daunting synthetic challenge. In the present work, the first example of efficient and selective oxidation of sulfides to sulfones and sulfoxides using molecular oxygen under clean conditions was established. The first example of selective oxidation of sulfides to sulfones and sulfoxides using molecular oxygen under clean conditions was established. The desired products could be easily collected through recrystallization in large-scale preparation.